Pengaruh Moderasi Brand Image terhadap Hubungan antara Promosi dan Loyalitas pada Pelanggan ShopeeFood di Magelang - Fitriani, Dewi; Novitaningtyas, Ivo (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
promotion affects loyalty with the brand image as a moderating variable. This study uses a quantitative approach with primary data obtained from respondents' responses through questionnaires and secondary data as reference material sourced from journals, articles, and books. The number of samples is 100 respondents who are ShopeeFood customers. Samples were taken based on the purposive sampling method. Data analysis using the SPSS tool. To test the hypothesis using multiple linear regression analysis and analysis of the interaction test of moderating variables. The results show that promotion has a positive and significant effect on loyalty, and brand image plays a role in strengthening the drive for loyalty. These results provide managerial implications for ShopeeFood to improve new strategies in promoting its products and strengthening its brand image so as to encourage customer loyalty. Thus, ShopeeFood is expected to be able to plan the right strategy, and attract and provide good service in order to create a positive brand image in the minds of consumers so that consumers have the potential to become loyal customers.